Urban geotourism in Salvador (Bahia, Brazil): a strategy for the promotion of geosciences education and geoconservation - Pinto, A. B. C. (2011)
In order to promote the geological tourism and geoconservation in Salvador city (Bahis, Brazil) an inventory of geosites is under development. These geosites, together with cultural places selected for the use of specific types of stones in historical buildings of the city centre will be the background for the implementation of an urban geostourism strategy in Salvador city.